Possible Ways to Overcome Antibiotic Resistance of Nosocomial Pathogens Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Stenotrophomonas maltophilia - N. N. Markelova; E. F. Semenova (Антибиотики и Химиотерапия)
Gram-negative bacteria Klebsiella pneumoniae, Acinecobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia are the most important nosocomial pathogens due to rapid growth of multiple drug resistance among them. This review contains the analysis of articles on characteristics of structural and physiological features of these pathogens as pathogens of nosocomial infections and connections between virulence and antibiotic resistance. New approaches and antibacterial agents, alternative to antibiotics, which help solve the problem of overcoming antibiotic resistance of gram-negative bacteria are described.